WAYANG DALAM KONTEKS BUDAYA - Muhammad Mukti (Imaji, 2006)
Wayang is a traditional drama performance, which has existed since the period of Erlangga. Its history then can be traced back from Majapahit, Demak, and the nine wali until this present time. In cultural context, especially that of Islam, wayang is a means to spread the Islamic religious teachings, leading people to God. As a medium of religious propagation, this performance always transforms the syahaadah sentences Laailaahailallah and Muhammadar-rasulullah. These can be sent explicitly or implicitly. Additionally, the ways to invite people to implement the teaching values are done directly or indirectly. Through this performance, the audience can observe the good conducts to be deduced as Islamic knowledge. Since the direction is from practices to knowledge, as a medium of propagation this performance is a set back. Keywords: wayang, cultural context, religious propagation